Re-envisioning Elvis from Sepilok (2007) as a globalised contemporary art criticism medium: in context to DAKEN 2021 / Musaddiq Mohamad Khalil … [et al.] - Mohamad Khalil, Musaddiq; Ibrahim, Diana; Khalip, Azahari; Wan Yaacob, Wan Mohd Zulkifle; Abdul Rahim, Ahmad Zuraimi (Faculty of Art and Design, 2024)
Contemporary art is addressed within the canons of art history as celebrating inclusiveness over exclusiveness in regards to the Body-of-Knowledge (BOK), as well as paradigms between societies. Over time such plural established relationships have coexisted as a pluriversal celebration that attracts responses and reactions by global contemporary artists towards globalised issues. The Malaysian Ministry of Tourism, Art, and Culture (MOTAC) launched the National Cultural Policy (DAKEN 2021) as an important entity that emphasises values of Inclusion, Togetherness, and Gratitude. The study aims to explore the work created by Azahari Khalip in 2007 entitled Elvis From Sepilok as a contemporary art criticism medium in-line with the DAKEN 2021 values, as well as establish its globalise significance in contemporary art at present content, and context, as an instructional medium currently adopted by the University of Leiden, Netherlands, through their international seminars and online courses in regards to topics of ‘Art in a Global Perspective’. The data in this research design study is collected using mixed methods of qualitative visual observation upon exploring the possibilities of the work as an art criticism medium, verified by local and global informants, and a quantitative non-probability sampling method, using convenient sampling strategy, acquired by a sampling frame of 300 respondents. The data are analysed by formal analysis using the Feldman Art Criticism Model, and Spearman Correlation Analysis upon establishing the significant correlational relationship between the work of art and DAKEN 2021 values. The results and findings generated possibilities for future researchers, and visual artists upon extracting local values as medium of contemporary art criticism, towards a globalised context.